The Diversity and Nitrogen Metabolism of Culturable Nitrate-Utilizing Bacteria Within the Oxygen Minimum Zone of the Changjiang (Yangtze River) Estuary - He, Wenxuan; Liu, Sizhen; Jiang, Zhichen; Zheng, Jinshui; Li, Xuegang; Zhang, Dechao (Frontiers in Marine Science, 2021)
The nitrogen cycle is an indispensable part of the biogeochemical cycle, and the reactions that occur in the ocean oxygen minimum zone (OMZ) mediate much of the loss of nitrogen from oceans worldwide. Here, nitrate-utilizing bacteria were isolated from the water column at 17 stations within the OMZ of the Changjiang (Yangtze River) Estuary using selective media and a culture-dependent method. The microbial diversity, nitrogen metabolism and nitrate reduction test of culturable heterotrophic bacteria were examined. A total of 164 isolates were obtained; they were mostly affiliated with Proteobacteria (81.1%), Actinobacteria (5.5%), Bacteroidetes (12.3%), and Firmicutes (0.6%). Pseudomonas aeruginosa, Sphingobium naphthae, and Zunongwangia profunda were found at most stations. Among 24 tested representative strains, 8 were positive for nitrate reduction; they belonged to genera Aurantimonas, Halomonas, Marinobacter, Pseudomonas, Thalassospira, and Vibrio. Pseudomonas aeruginosa contained the genes (napAB, norBC, nirS, and nosZ) for complete denitrification and may be responsible for mediating denitrification. 66% representative isolates (16/24) contained genes for reducing nitrate to nitrite (nasA, napAB, or narGHI) and 79% representative isolates (19/24) possessed genes for converting nitrite to ammonia (nirA or nirBD), suggesting that nitrate and nitrite could act as electron acceptors to generate ammonium, subsequently being utilized as a reduced nitrogen source. This study improves our understanding of the microbial diversity within the OMZ of Changjiang Estuary and may facilitate the cultivation and exploitation of bacteria involved in the nitrogen cycle.